GROUNDWATER USE ZONING MAPPING USING GEOMORPHOLOGICAL APPROACH FOR HANDLING THE WATER CRISIS: STUDY CASE OF KECAMATAN PAGAK, KABUPATEN MALANG - Damar Panoto; Irfan Helmi Pradana; Melinda Meganagatha Rosbella Devy; Didik Taryana (USN Kolaka, 2020)
Kecamatan Pagak, Kabupaten Malang is an area which is dominated by karst landform. Basically, Karst is landform which is vulnerable to drought for the very minimum of waterflow surface. Underground river flows are more developed in karst landforms due to the large number of fractures. Based on these problems, this research seeks to solve the problem of water crisis in karst landforms by utilizing groundwater. It chose geomorphological approach to find the highly potential groundwater landforms so that these they can be used as groundwater infiltration zones. Geomorphological mapping is carried out by identifying aspects of morphology, morphogenesis, morphoarrangement, and morphocronology. Through the geomorphological mapping, it was obtained nine units of landforms in the research area. The P4Fv1 landforms are units that have high groundwater potential which can be utilized in large quantities.